2019
DOI: 10.1002/arch.21638
|View full text |Cite
|
Sign up to set email alerts
|

Midgut transcriptome analysis of Clostera anachoreta treated with lethal and sublethal Cry1Ac protoxin

Abstract: Clostera anachoreta is one of the important Lepidoptera insect pests in forestry, especially in poplars woods in China, Europe, Japan, and India, and so forth, and also the target insect of Cry1Ac toxin and Bt plants. Six genes, HSC70, GNB2L/RACK1, PNLIP, BI1‐like, arylphorin type 2, and PKM were found in this study, and they might be associated with the response to the Cry1Ac toxin, found by analyzing the transcriptome data. And the PI3K‐Akt pathway was highly enriched in differentially expressed unigenes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…ABC transporters play an important role in Bt‐toxin poisoning and resistance in insect (Atsumi et al, 2012; Gahan et al, 2010; Tay et al, 2015). A large number of research found that ABC transporters changed their expression after Bt‐toxin treatment (Lei et al, 2014; Liu et al, 2020). Unsurprisingly, it was found that seven ABC transporters were significantly changed between Cry1Ac treatment group and control group, including ABCA2 (BMSK0007991), ABCA3 (BMSK0010069), ABCC4 (BMSK0008667), ABCF1 (BMSK0008549), ABCF4 (BMSK0009342), ABCG4 (BMSK0006983), and ABCG1 (BMSK0006984)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ABC transporters play an important role in Bt‐toxin poisoning and resistance in insect (Atsumi et al, 2012; Gahan et al, 2010; Tay et al, 2015). A large number of research found that ABC transporters changed their expression after Bt‐toxin treatment (Lei et al, 2014; Liu et al, 2020). Unsurprisingly, it was found that seven ABC transporters were significantly changed between Cry1Ac treatment group and control group, including ABCA2 (BMSK0007991), ABCA3 (BMSK0010069), ABCC4 (BMSK0008667), ABCF1 (BMSK0008549), ABCF4 (BMSK0009342), ABCG4 (BMSK0006983), and ABCG1 (BMSK0006984)).…”
Section: Resultsmentioning
confidence: 99%
“…DEGs between Cry1Ac susceptible and resistance strains of Helicoverpa armigera were significantly enriched in ABC transporter pathway (Wei et al, 2018). RNA‐Seq data showed that ABCC4 and ABCG1 can be activated by Cry1Ac in Clostera anachoreta (Liu et al, 2020). In our data, it was observed that the expression of ABCA2, ABCA3, ABCC4, and ABCG4 were significantly upregulated in Cry1Ac treatment group.…”
Section: Discussionmentioning
confidence: 99%
“…In that sense, a previous study provided insight into a novel ABC transporter gene PxABCH1 in diamondback moth, Plutella xylostella (L.), and revealed it as an excellent target for RNAi‐based insect pest control and resistance management (Guo et al, 2015). A Cadherin‐like protein is also a potential receptor of Bt toxins, and its down‐regulated expression or mutation is one of the main causes of resistance in pests (Liu et al, 2019). Additional work is necessary to unravel whether some of the outlier SNP markers detected in this study indeed have biological significance (Barrett & Hoekstra, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…We found the LC50 dose of Bt infection could suppress the humoral immune response in the third instar larvae of Plutella xylostella [ 80 ]. Growing evidence suggests that Bt-induced immunity is a dose-dependent effect [ 88 , 89 , 90 , 91 ].…”
Section: The Host Immune System In Response To Bt Infectionmentioning
confidence: 99%